Practical application of lithium-ion battery management systems: heating system - Zraibi, Brahim; Mansouri, Mohamed; Ezzahi, Abdelghani (Institute of Advanced Engineering and Science, 2025)
This paper presents a lithium-ion battery management system (BMS) aimed at improving battery longevity through hardware and software optimization. The system targets enhancing energy efficiency in heating devices like burners, commonly used in industrial and domestic applications. A key innovation is the modification of the Arduino Pro Mini 8 MHz 3.3 V microcontroller to reduce power consumption during sleep mode. The study evaluates two iterations of the system: an initial manually soldered prototype using the Arduino board and a second iteration with a robust printed circuit board assembly (PCBA). The transition to the PCBA improved system efficiency and eliminated connection issues. The development integrates conventional circuitry and modern software strategies for efficient battery charge/discharge management. Results from both prototypes demonstrate significant improvements in battery life, offering a sustainable solution for energy-efficient applications.